(untitled) - Murray, Bob (New York, 2006)
Raising an Optimistic Child offers you tools for creating a positive, supportive family atmosphere that helps children who are already depressed and can even prevent this crippling disorder. Steps and additional techniques will help you combat your own depression, tackle parental issues, and enhance learning and coping skills. It also alerts you to circumstances that put a child at risk for depression and suggests ways to ward it off
Keywords: Child psychology,Depression in children,Child rearing,Parenting,Trầm cảm ở trẻ em,Nuôi dạy con; Psychological aspects,Psychological aspects,Các công trình phổ biến,Các khía cạnh tâm lý